Rotations, 3D equilibrium, and force-aft torques in alpine skiing - Brown, C. A.; LeMaster, R. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: This paper examines the conditions for equilibrium in 3 dimensions during a turn based on Euler's equations for rigid body dynamics. This advances the understanding of some of the positions skiers instinctively adapt to maintain line and balance in the absence of adequate fore-aft motion or torques. This understanding can assist in addressing root problems as opposed to reactions, or symptoms, in coaching.